Journey to Topaz a story of the Japanese-American evacuation. - Uchida, Yoshiko (Creative Arts Book Company, 1985)
After the Pearl Harbor attack an eleven-year-old Japanese-American girl and her family are forced to go to an aliens camp in Utah.